The Influence Of Islamic Boarding School Accounting Understanding, HR Competence And Islamic Boarding School Accountability Training On Islamic Boarding School Financial Accountability - Burhan Burhan; Nanda Suryadi; Arie Yusnelly; Sindi Yulianti (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The purpose of this study was to determine the effect of Islamic boarding schools' accounting understanding, HR competence, and Islamic boarding school accounting training on the financial accountability of Islamic boarding schools. While the population used in this study were all Islamic boarding schools in Rokan Hulu Regency, totaling 36 Islamic boarding schools. The samples in this study were Islamic boarding school managers such as foundation leaders, school principals, treasurers and principals, so that 68 respondents were obtained using a purposive sampling technique. The data used are primary and secondary data. The data analysis technique used in this study is to use the Partial Least Square (PLS) approach with the SmartPLS 4 software tool to examine the relationship between variables. The test results show that: Islamic Boarding School Accounting Understanding has a positive and significant effect on Islamic Boarding School Financial Accountability in Rokan Hulu District, HR Competence has no significant positive effect on Islamic Boarding School Financial Accountability in Rokan Hulu District, and Islamic Boarding School Accounting Training has a significant positive effect on Financial Accountability of Islamic Boarding Schools in Rokan Hulu District.